The Influence of KH. Hasyim Asy'ari's Moderate Political Thought on Efforts to Counter the Radicalism Movement in Indonesia - Hermawan, Andi; Kesuma, Arsyad Sobby; Yudha, Gesit (JPW (Jurnal Politik Walisongo), 2024)
The roots of radicalism among Muslims are often associated with religious beliefs. However, radicalism can arise from various factors, including economic, political, and social. This study focuses on the discussion of the influence of KH. Hasyim Asy'ari's moderate political thinking on efforts to overcome radicalism movements in Indonesia, namely focusing more on the moderate political side and efforts to overcome radicalism. This study aims to analyze the contribution and influence of KH. Hasyim Asy'ari's moderate political thinking in efforts to overcome radicalism. The method used in this study is descriptive qualitative. The research in this article uses a library research method or also known as the library research study method, namely a strategy for collecting information through the introduction of relevant theories and literature. KH. Hasyim Asy'ari emphasized four principles in society to prevent radicalism: tawasuth and i'tidal (moderate and fair attitudes), tasamuh (tolerance), tawazun (balance), and amar ma'ruf nahi munkar (encouraging goodness and preventing harm). This study contributes a conceptual framework that Islamic moderation based on the pesantren tradition can be an effective instrument in deradicalization. The thoughts of KH. Hasyim Asy'ari not only represent the legacy of classical Islamic knowledge, but also show the adaptive capacity of Islam in facing modern socio-political dynamics. Thus, the moderate political thoughts of KH. Hasyim Asy'ari are relevant as references in developing sustainable educational strategies and ideological policies in the context of Indonesia and the wider Islamic world.